Participation of civil society in public administration: Prospects for international experience implementation in Ukraine - Біла-Тіунова, Любов Романівна; Біла-Тіунова, Л. Р.; Била-Тиунова, Любовь Романовна; Bila-Tiunova, Liubov R.; Білоус-Осінь, Тетяна Ігорівна; Білоус-Осінь, Т. І.; Билоус-Осень, Татьяна Игоревна; Bilous-Osin, Tetiana I.; Козачук, Діана Анатоліївна; Козачук, Д. А.; Козачук, Диана Анатольевна; Kozachuk, Diana A.; et al. (Maya Global Education Society, 2019)
Purpose: Determination of possible ways to increase the effectiveness of interaction between civil society institutions and public administration subjects in Ukraine through the use of international experience; determination of a unified concept of management humanization and democratization and proposal of specific recommendations for reforming the existing public administration system in Ukraine. Methodology: General and specific methods of scientific knowledge were applied during the research: a system analysis method, a dialectical method, a formal-logical method, a structural-functional method, and empirical methods. Result: The authors concluded that there is poor interaction between the public administration subjects and the civil society institutions in Ukraine. In order to increase the positive effect of introducing new forms of civil participation in public administration, it is important to popularize citizens’ e-participation in public administration. Free access to the electronic reflection of activities of any public administration subject allows simplifying public participation in making specific decisions. Applications: The results of the research are believed to be interesting and useful for domestic legislators and public administration subjects at actualization of tendencies to administration democratization and humanization. Novelty/Originality: The results are obtained independently and original (no analogues or incorrect borrowings). The research subject is considered in Ukraine for the first time and seems to be prospective for further development.

Мета: Визначення можливих шляхів підвищення ефективності взаємодії між інститутами громадянського суспільства та суб'єктами державного управління в Україні шляхом використання міжнародного досвіду; визначення єдиної концепції гуманізації та демократизації управління та пропозиція конкретних рекомендацій щодо реформування існуючої системи державного управління в Україні. Методологія: Під час дослідження застосовувалися загальні та специфічні методи наукового пізнання: метод системного аналізу, діалектичний метод, формально-логічний метод, структурно-функціональний метод, емпіричні методи. Результат: Автори дійшли висновку про слабку взаємодію суб'єктів державного управління та інститутів громадянського суспільства в Україні. Для підвищення позитивного ефекту від впровадження нових форм громадянської участі в державному управлінні важливо популяризувати електронну участь громадян у державному управлінні. Вільний доступ до електронного відображення діяльності будь-якого суб'єкта державного управління дозволяє спростити участь громадськості у прийнятті конкретних рішень. Практичне застосування: результати дослідження вважаються цікавими та корисними для вітчизняних законодавців та суб'єктів державного управління при актуалізації тенденцій до демократизації та гуманізації управління. Новизна/Оригінальність: результати отримані самостійно та є оригінальними (без аналогів чи неправильних запозичень). Тема дослідження розглядається в Україні вперше і видається перспективною для подальшого розвитку.
Bila-Tiunova L. Participation of civil society in public administration: Prospects for international experience implementation in Ukraine / L. Bila-Tiunova, T. Bilous-Osin, D. Kozachuk, V. Vasylkivska // Humanities and Social Sciences Reviews. - Maya Global Education Society, 2019. - Vol. 7. - Issue 5. - P. 757-764.
Keywords: civil society; participation form; public administration; institutional and legal principles; social and economic principles; international standards; громадянське суспільство; форма участі; державне управління; інституційно-правові принципи; соціально-економічні принципи; міжнародні стандарти; Research Subject Categories::LAW/JURISPRUDENCE